2017
DOI: 10.1155/2017/8689017
|View full text |Cite
|
Sign up to set email alerts
|

Intrastromal Corneal Ring Segments for Astigmatism Correction after Deep Anterior Lamellar Keratoplasty

Abstract: Background. To evaluate the change in corneal astigmatism after intrastromal corneal ring segment (ICRS) implantation in keratoconus patients with previous deep anterior lamellar keratoplasty (DALK). Design was a longitudinal, retrospective, interventional study. The study included 25 eyes of 24 patients with keratoconus who had DALK performed at least two years prior to ICRS implantation. All patients had a clear corneal graft with up to 8.00 D of corneal astigmatism and intolerance to contact lenses. The stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
31
2
19

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(56 citation statements)
references
References 33 publications
4
31
2
19
Order By: Relevance
“…The 49% correction rate of the combination compares favorably with all studies of PRK (range of correction rate: 21% to 37%) and most studies of ICRS. 14,16,18,19,21–35 To our knowledge, only 2 studies of ICRS showed similar results (50% and 51%) but reported preoperative astigmatism below 4.0 D, whereas we reported a mean preoperative value of 7.88 ± 2.13 D. 17,20…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…The 49% correction rate of the combination compares favorably with all studies of PRK (range of correction rate: 21% to 37%) and most studies of ICRS. 14,16,18,19,21–35 To our knowledge, only 2 studies of ICRS showed similar results (50% and 51%) but reported preoperative astigmatism below 4.0 D, whereas we reported a mean preoperative value of 7.88 ± 2.13 D. 17,20…”
Section: Discussionmentioning
confidence: 49%
“…[16][17][18][19][20][21] In addition, the ICRS studies reporting the lowest preoperative Kmax readings were the ones to report greater flattening. 16,17,19,20 Accordingly, we found a negative correlation between the preoperative Kmax and the improvement in both CDVA and ASTac. In our series, the safety protocol was a limiting factor in planning the ICRS thickness, which is directly related to corneal flattening.…”
Section: Discussionmentioning
confidence: 99%
“…When these methods fail, surgery is indicated to improve the corneal surface. When the cornea is transparent, implantation of polymethylmethacrylate (PMMA) intrastromal ring segments can be a successful option 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Cuando estos métodos fallan, está indicada la cirugía para mejorar la superficie corneal. Cuando la córnea se mantiene transparente, la implantación de segmentos de anillos intrastromales de polimetilmetacrilato (PMMA) puede ser una opción exitosa 6 .…”
Section: Introductionunclassified